The Flax Genome - You, Frank M.; Fofana, Bourlaye (Cham : Springer International Publishing : Imprint: Springer, 2023)
The Flax Genome is a comprehensive compilation of most recent studies focused on reference genome, genetic resources and molecular diversity, breeding, QTL mapping, gene editing tools, functional genomics and metabolomics, molecular breeding via genomic selection, and genomic resources. The flax genome reference sequences and the new genome assemblies are presented. A list of flax QTL and candidate genes associated with more than 35 traits, including yield and agronomic, seed quality and fatty acid composition, fibre quality and yield, abiotic stress, and disease resistance traits, are summarized. A QTL- based genomic selection strategy and genome-editing tools are systematically introduced. In addition, huge amounts of flax genomic resources generated in the last decade are summarized. The book contains 13 chapters with about 390 pages authored by globally reputed researchers in the relevant fields to this crop The book is intended to be useful to students, teachers, and researchers interested in traditional and molecular breeding, pathology, molecular genetics and breeding, bioinformatics and computational biology, and functional genomics.
Reference genome sequence of flax -- Repeat DNA sequences in flax genomes -- Pale flax (Linum bienne): an underexplored flax wild relative -- Flax breeding -- QTL mapping: strategy, progress and prospects in flax -- Genetics of abiotic stress in flax. QTL and candidate genes for flax disease resistance -- Key stages of flax bast fiber development through the prism of transcriptomics -- Metabolomics and transcriptomics-based tools for linseed improvement.
Keywords: Botany; Genetics; Biotechnology; Plant Science; Genetics and Genomics; Biotechnology